Election of Cooperative Chairman Using the Moora Method (Multi Objective Optimization On The Basis Of Ratio Analysis) - Purba, Megaria; Simarmata, Ratih Iren; Malini, Malini (Information Technology and Science (ITScience), 2023)
The Padrepio Helvetia Medan Parish Mandiri Savings and Loans Association Cooperative is one of the cooperatives engaged in the savings and loan sector by prioritizing members' desire to save so that they can create joint capital for members to borrow with appropriate loan services for welfare purposes. The Annual Members' Meeting is an annual agenda as a media for management to be accountable for their performance for one year. The chairman of the cooperative is the highest structural position of the administrator who has duties and responsibilities both inside and outside the cooperative in controlling all cooperative activities. The process of electing the chairman of the Padre Pio Parish Savings and Loans Association cooperative is still being carried out only by pointing to and mentioning someone's name from among the names of the management and then conveying it to members to approve. The determination of the chairman which is carried out using the arbitrary model is not in accordance with the terms and criteria of an optimal cooperative chairman because the elected chairman is not necessarily the most competent of the candidates and often happens just because of friendship so the results are not objective. With the reasons described, the researcher applied the MOORA method. The application of the MOORA method to the election of the chairman of the Padre Pio Helvetia Medan Parish Independent Savings and Loans cooperative can help determine a more objective chairman based on terms and criteria by solving problems through complex mathematical calculations, determining the weight value for each attribute, then proceed with the ranking process which will select the alternative that has been given. In this study the criteria determined consisted of background and educational level, certificate ownership, age, and length of time being a member. In the objective approach, the weight value is calculated mathematically so that it ignores the subjectivity of the decision maker. With the application of the MOORA method, several alternatives that meet the requirements and criteria can be determined which is the best to serve as chairman. The best ranking results are those who are most worthy of being the head of a more objective cooperative.